2021
DOI: 10.1002/dta.3123
|View full text |Cite
|
Sign up to set email alerts
|

The use of RNA‐based 5'‐aminolevulinate synthase 2 biomarkers in dried blood spots to detect recombinant human erythropoietin microdoses

Abstract: The hematological module of the Athlete Biological Passport (ABP) is used for indirect detection of blood manipulations; however, the use of this method to detect doping, such as with microdoses of recombinant human erythropoietin (rhEPO), is problematic. For this reason, the sensitivity of ABP must be enhanced by implementing novel biomarkers. Here, we show that 5'-aminolevulinate synthase 2 (ALAS2) mRNAs are useful transcriptomic biomarkers to improve the indirect detection of rhEPO microdosing. Moreover, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…In this study, since the amount of circulating EPO hormone increased in our mouse model, we assumed that the RNAs in whole-blood samples from the model were showing the same fluctuations as those reported in the studies described above. The total RNA-seq results were largely consistent with the expression patterns described in previous reports [57][58][59] (Supplementary Figure S6). In particular, five genes (Bcl2l1, Epb42, Slc4a1, Tmod1, and Trim58) that were analyzed as ABP candidate parameters in the previous study by Wang et al [58] showed a clear increase of about 2-4 times the average value, which was statistically significant (Supplementary Figure S6).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, since the amount of circulating EPO hormone increased in our mouse model, we assumed that the RNAs in whole-blood samples from the model were showing the same fluctuations as those reported in the studies described above. The total RNA-seq results were largely consistent with the expression patterns described in previous reports [57][58][59] (Supplementary Figure S6). In particular, five genes (Bcl2l1, Epb42, Slc4a1, Tmod1, and Trim58) that were analyzed as ABP candidate parameters in the previous study by Wang et al [58] showed a clear increase of about 2-4 times the average value, which was statistically significant (Supplementary Figure S6).…”
Section: Discussionsupporting
confidence: 89%
“…A previous study reported the findings obtained after administration of recombinant hEPO (rhEPO) to humans and transcriptome analysis using whole-blood RNA [57]. The RNAs of ABP parameter candidates found in that study [57] were also investigated in detail in other studies and could be recognized as robust biomarker RNA candidates for detecting rhEPO-administered doping [58,59]. In this study, since the amount of circulating EPO hormone increased in our mouse model, we assumed that the RNAs in whole-blood samples from the model were showing the same fluctuations as those reported in the studies described above.…”
Section: Discussionmentioning
confidence: 91%
“…DBS is a complementary approach to traditional urine and venous blood matrices, which can facilitate simpler sample collection and increase the number of samples available for biomarker analysis due to reduced costs. Loria et al 7 The theme of differentiation is further explored by Ishii et al 13 for a biomarker approach to distinguish nicotine administration from tobacco exposure in horses. Both trans-3 0 -hydroxycotinine and anatabine could be used as potential biomarkers in equine urine and plasma to indicate recent exposure to tobacco products in horses.…”
mentioning
confidence: 99%
“…The potential use of dried blood spots (DBS) for biomarker analysis is presented by Rocca et al 6 and Loria et al 7 for improved detection of recombinant erythropoietins. DBS is a complementary approach to traditional urine and venous blood matrices, which can facilitate simpler sample collection and increase the number of samples available for biomarker analysis due to reduced costs.…”
mentioning
confidence: 99%
See 1 more Smart Citation